Researcher Electrical Energy Generated from Native Plants Wastes - VANGCHANGYIA, Somsack; SOUADA, Paoxiong; VONGVILAY, Chanpheng; CHOUALUEHER, Sivone; KEOMANYCANH, Phonepadith; PHIPHATPHON, Soudavone; PHAIGNAVONG, Somchay; CHOUMO, Yelee; SILIVANH, Sommay (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
In this experiment, the team extracted 300 mL of electrolyte water from local plants and placed the anode and cathode of 40 cm as a cell, using a multimeter to measure the voltage and current every 5 minutes up to 30 minutes. In the beginning, the voltage of the electrolytes of lemons, mangosteen, star apple, and fermented plants can be measured at 1V, while pineapple, star fruit, and star gooseberry were 0.9V, and at the end of 30 minutes, the electrolytes of lemons, mangosteen, and star apple were 0.9V and the electrolytes of pineapple, star fruit, Star gooseberry, and fermented plants were 0.8V, 0.8V, 0.6V and 0.7V respectively. For the current at the beginning, electrolytes of pineapple, lemons, and mangosteen can be measured at 50mA, while other electrolytes were 25mA. The current gradually decreases according to the process of chemical bonding of the electrolytes with the copper plate. After 30 minutes, the final values of current were 16mA, 8mA, 11mA, 15mA, 12mA, 14mA, and 11mA respectively. From the voltage and current values, the electric power from pineapple, lemons, star fruit, and fermented plants can be calculated at the beginning as 0.045 w, 0.05 w, 0.05 w, and 0.05 w respectively. After 30 minutes, the remaining electric power of lemons, star apple, and mangosteen were 0.01w, 0.01w, and 0.013w. While pineapple, star fruit, star gooseberry, and fermented plants were 0,006 W and 0,007 W.